2018
DOI: 10.2967/jnumed.118.209007
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of 18F-FDG Dose Reductions in Breast Cancer PET/MRI

Abstract: The goal of this study was to determine the level of clinically acceptable F-FDG dose reduction in time-of-flight PET/MRI in patients with breast cancer. Twenty-six consecutive women with histologically proven breast cancer were analyzed (median age, 51 y; range, 34-83 y). Simulated dose-reduced PET images were generated by unlisting the list-mode data on PET/MRI. The acquired 20-min PET frame was reconstructed in 5 ways: a reconstruction of the first 2 min with 3 iterations and 28 subsets for reference, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…For the qualitative evaluation, each observer read the total pool of 220 images, rating each on a 4-point scale according to 3 criteria: image noise, image sharpness, and general image quality-this scheme was similar to previously published criteria [30]. Additionally, for each patient full-count image, the observer selected locations of liver, lung, and blood pool (left ventricle or aorta) to be used subsequently for volume-of-interest (VOI) analyses, in which spherical VOIs, of radius 10 mm for liver and lung and 5 mm for blood pool, were defined and propagated throughout the reduced-count images for each patient.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…For the qualitative evaluation, each observer read the total pool of 220 images, rating each on a 4-point scale according to 3 criteria: image noise, image sharpness, and general image quality-this scheme was similar to previously published criteria [30]. Additionally, for each patient full-count image, the observer selected locations of liver, lung, and blood pool (left ventricle or aorta) to be used subsequently for volume-of-interest (VOI) analyses, in which spherical VOIs, of radius 10 mm for liver and lung and 5 mm for blood pool, were defined and propagated throughout the reduced-count images for each patient.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…A number of developments are currently being pursued for lowering the injected activities and/or PET recording times [29][30][31]. Recent studies have proposed appropriate regularization schemes to more effectively limit the increase in noise level [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond MRI advances, new PET-detector technologies allowing for significantly reduced amounts of injected radiotracer offer considerably improved flexibility in acquisition time versus radiation burden (69,70). Sah et al, for example, demonstrated that the amount of injected radiotracer can be reduced to 5%-10% of the currently clinically accepted standard dose while maintaining image quality (71). However, that study evaluated breast lesions with favorably low background on PET.…”
Section: Advances In Workflowmentioning
confidence: 99%